Upper Extremity Deep Vein Thrombosis and Asymptomatic Vein Occlusion in Patients With Transvenous Leads: A Systematic Review and Meta-Analysis - Duijzer, Daniël; de Winter, Maria A.; Nijkeuter, Mathilde; Tuinenburg, Anton E.; Westerink, Jan (Frontiers in Cardiovascular Medicine, 2021)
Aims: The presence of transvenous leads for cardiac device therapy may increase the risk of venous thromboembolisms. The epidemiology of these complications has not yet been determined systematically. Therefore, this study aims to determine (I) the incidence of symptomatic upper extremity deep vein thrombosis (UEDVT) and (II) the prevalence of asymptomatic upper extremity vein occlusion in patients with transvenous leads, both after the initial 2 months following lead implantation. Methods: PubMed, EMBASE and Cochrane Library were searched until March 31, 2020 to identify studies reporting incidence of UEDVT and prevalence of asymptomatic vein occlusion after the initial 2 months after implantation in adult patients with transvenous leads. Incidence per 100 patient years of follow-up (PY) and proportions (%) were calculated to derive pooled estimates of incidence and prevalence. Results: Search and selection yielded 20 and 24 studies reporting on UEDVT and asymptomatic vein occlusion, respectively. The overall pooled incidence of UEDVT was 0.9 (95% CI 0.5 – 1.4) per 100PY after 2 months after lead implantation. High statistical heterogeneity was present among studies (I2 = 82.4%; P = <0.001) and only three studies considered to be at low risk of bias. The overall pooled prevalence of asymptomatic upper extremity vein occlusion was 8.6% (95% CI 6.0 – 11.5) with high heterogeneity (I2 = 81.4%; P = <0.001). Meta-regression analysis showed more leads to be associated with a higher risk of UEDVT. Conclusion: Transvenous leads are an important risk factor for symptomatic UEDVT, which may occur up to multiple years after initial lead implantation. Existing data on UEDVT after lead implantation is mostly of poor quality, which emphasizes the need for high quality prospective research. Asymptomatic vein occlusion is present in a substantial proportion of patients and may complicate any future lead addition.